If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -3) = 7x + 15 Reorder the terms: 5(-3 + 2x) = 7x + 15 (-3 * 5 + 2x * 5) = 7x + 15 (-15 + 10x) = 7x + 15 Reorder the terms: -15 + 10x = 15 + 7x Solving -15 + 10x = 15 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -15 + 10x + -7x = 15 + 7x + -7x Combine like terms: 10x + -7x = 3x -15 + 3x = 15 + 7x + -7x Combine like terms: 7x + -7x = 0 -15 + 3x = 15 + 0 -15 + 3x = 15 Add '15' to each side of the equation. -15 + 15 + 3x = 15 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = 15 + 15 3x = 15 + 15 Combine like terms: 15 + 15 = 30 3x = 30 Divide each side by '3'. x = 10 Simplifying x = 10
| 11x-15=40 | | 3f-12=3(f+12) | | 5.25+15=46.50 | | 8x-3=3x-7 | | -4r+4r=8-4r+3r | | 130+40c=270 | | 4b-11=5 | | 15x-54=66 | | 3t^2-14t-22=0 | | (4x-1)(2x^2+3)= | | 64x^2-644x+1552=0 | | -6x+3=-39 | | .3x+5=6 | | k+9=6(k-1) | | 49=(-9y)-68 | | 130+40c=130 | | 3(4x^2-49)=27 | | 2-3x=x+y+2 | | 2+3ln(x+1)=4 | | -2v-4v=12 | | 12x+4[8-4(2x+4)]=4x-8 | | 8a-(-3-5a)= | | -12.5=2.5+4x | | -93+5x=116-6x | | -2v-9v=12 | | -4+4r=8-4r+3r | | 40=.5t-4.9t^2 | | -10x+15=2x^2-7x-12 | | -2x+6+3x=13 | | 12+2a-8a=42 | | 2yq+5(x+4)+6x= | | 5x+30=6x-50 |